2009
DOI: 10.1021/la901622c
|View full text |Cite
|
Sign up to set email alerts
|

Polysiloxane Surfactants for the Dispersion of Carbon Nanotubes in Nonpolar Organic Solvents

Abstract: We develop two new amphiphilic molecules that are shown to act as efficient surfactants for carbon nanotubes in non-polar organic solvents. The active conjugated groups, which are highly attracted to graphene nanotube surface, are based on pyrene and porphyrin. We show that relatively short (C18) carbon tails are insufficient to provide stabilization. As our ultimate aim is to disperse and stabilize nanotubes in siloxane matrix (polymer and crosslinked elastomer), both surfactant molecules were made with long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…Lastly, the molecular structure associated with the π−π stacking complex can vary considerably depending on the location of the rigid π-bondings. They can be in a block [54][55][56][57], or in the backbone [58]. The resultant supramolecular structure is usually formed to maximize the π-stacking interaction, inducing alignment of the π bonding with respect to the CNT chirality.…”
Section: Thermodynamically Stable Dispersion Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, the molecular structure associated with the π−π stacking complex can vary considerably depending on the location of the rigid π-bondings. They can be in a block [54][55][56][57], or in the backbone [58]. The resultant supramolecular structure is usually formed to maximize the π-stacking interaction, inducing alignment of the π bonding with respect to the CNT chirality.…”
Section: Thermodynamically Stable Dispersion Statesmentioning
confidence: 99%
“…Especially, surfactants designed for non-polar organic solvent are rare, and a pyrene-siloxane based surfactant is only recently developed [57]. Table 1.…”
Section: Thermodynamically Stable Dispersion Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive discussion of surfactant optimisation and the details of synthesis of the pyrene-siloxane molecule PySi70 are described in an earlier paper. 25 The multi-wall CNTs were dispersed in petroleum ether (boiling point 40-60 C) in the presence of PySi70 (PySi70 : CNT ¼ 60 : 1 by weight). A vial of the dispersion was left idle for 2 days, after which the upper 90% that contained creamed impurities was carefully removed.…”
Section: Cnt Suspension Preparationmentioning
confidence: 99%
“…It is well known that organo‐functionalized silanes have been widely used as coupling agents to improve the total adhesive strength of organic and inorganic substrates . One of the most known bifunctional silanes is vinyltriethoxysilane (VTES), which has hydrolysable methoxy groups as well as one vinyl group attached to silicon, this imparts additional chain flexibility and improves the adhesive properties against substrates such as glass and carbon nanotubes . Yuen et al reported the poly(vinyltriethoxysilane) modified multi‐walled carbon nanotube (PVTES‐MWCNT)/PI nanocomposites .…”
Section: Introductionmentioning
confidence: 99%